Dietary change revealed in kitchen refuse pits from the ancient floors of Housepit 54, K'etxelknáz (Bridge River Site), British Columbia - Prentiss, Anna Marie; Hampton, Ashley; Larmon, Jeannie; Denis, Megan; Foor, Thomas A.; O'Brien, Haley; Goodale, Nathan; Walsh, Matthew J.; Edwards, Alysha; Jack, Joshua; Ryan, Ethan (Frontiers in Nutrition, 2026)
IntroductionDietary change in traditional fishing and foraging societies has been examined from standpoints of resource accessibility, population demands, and social needs. Typically, scholars focus on singular models to explain diet choice including those from optimal foraging theory, socio-ecology, and political and historical ecology. It is far less common that we are able to evaluate multiple factors affecting shifting diets and associated cooking procedures within a singular archaeological context.MethodsIn this paper, we draw data from the contents of deep pits filled with kitchen refuse from the 15 stratified anthropogenic floors of Housepit 54, Bridge River Site (K'etxelknáz), British Columbia. We distinguish refuse pits from sequentially re-used cache pits drawing on sediment micromorphology, sediment geochemistry, and general pit contents. Then, focusing on the refuse-filled pits, we develop direct insight into kitchen activities by examining variation in faunal and floral remains and geochemical signatures. Multivariate analysis allows us to recognize patterns of co-associations between faunal remains. Botanical remains and geochemical signatures provide additional support for conclusions regarding food procurement and processing. Temporal change in kitchen regimes is compared to trends in regional climate, local population, and house-level social change to assess alternative explanatory models.Results and discussionResults implicate the effects of variation in choice of prey and associated processing and transport procedures as primarily related to population and climate-related foraging pressures.